Detecting ROM changes using KINOVEA after muscle decontracture technique - Popa Vlad; Sandor Iosif; Ciocoi-Pop Dumitru Rareș (Sport şi Societate)
On a group of 25 healthy individuals, with tried to assess range of motion (ROM) before and afterapplyinga muscle tone reducing technique. We already know that thesetypestechniques are efficient and by using them we are able to influence the overall mobility of the areas to which they were applied. The tool utilised by us to detect changes in ROM were Kinovea, an open-source and free software. After assessing the mobility of the cervical region in a longitudinal axistwice,we used paired T tests to check in every instance what the statistical significance would be.We can conclude that Kinovea was in fact a software that could easily detect ROM alteration. Also, we could observe that the muscle decontracture technique was crucial in helping us having different results movement wise.